The remediation of Kruger Cave: A Later Stone Age and living heritage site in the western Magaliesberg - Justin Bradfield; Emma Cleminson; Christopher Hodgson; Renette Naudé; Liteboho Senyane; Bacara Spruit; Natalie Taylor; Lerato Tsakatsi; Stephan Woodborne; Matt G. Lotter (Southern African Field Archaeology)
We report on a programme of work to remediate Kruger Cave, a Later Stone Age painted rock shelter in the western Magaliesberg, South Africa. Kruger Cave, originally excavated in the 1980s and never backfilled or stabilised, has deteriorated through forty years of erosional and quotidian processes that have significantly reduced the extent of the archaeological deposit. The cave is currently occupied by a lay Christian pastor whose activities at the site place the remaining archaeological deposit at further risk. Remedial work was undertaken on what remains of the archaeology-bearing sediment. We also present the preliminary analysis from two small-scale excavations that aimed to document the site’s stratigraphy. We explore the ambivalence of Kruger Cave’s living heritage status within the context of current heritage management practices and discuss how our remedial work is designed to be responsive and respectful to both the archaeological and living heritage priorities.